COMPARISON OF SURGICAL TECHNIQUES FOR BENIGN PROSTATIC HYPERPLASIA: OUTCOMES AND INNOVATIONS (International journal of medical sciences, 2025)
Benign prostatic hyperplasia (BPH) is a prevalent condition among aging men, characterized by nonmalignant enlargement of the prostate leading to lower urinary tract symptoms (LUTS). Surgical intervention remains the gold standard for patients with moderate to severe symptoms unresponsive to medical therapy. This article compares conventional and minimally invasive surgical techniques, including transurethral resection of the prostate (TURP), holmium laser enucleation (HoLEP), photoselective vaporization (PVP), and robotic-assisted simple prostatectomy (RASP). Advances in laser technology and minimally invasive approaches have significantly reduced morbidity, hospitalization, and catheterization time while maintaining comparable efficacy to TURP.